التحالف بين الدول الإسلامية في العصر الحاضر : دراسة تحليلية مقاصدية - درمكي، علي محمد هاشم محمد (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2020)
This study examines Islamic collation in addressing risks that threaten, not only Muslims, but the whole world as well. The Islamic collation deals with security issues and the media and political vacuum through co-operations between countries to fight the epidemic of extremism and terrorism that have engulfed the world in general and the Islamic world in particular. This study highlights the textual evidence from the Holy Quran and the prophetic Hadith which are compatible with the main goals which the collation seeks to achieve,: security, stability, preventing aggression, preserving the main Islamic basics and maintaining good reputation of the Muslims worldwide by adopting moderate Islam and achieving world peace. The idea of the Islamic collation is an initiative that deserves support and enforcement. The methodology of the study varies between the historic and induction methods of the collations in addition to the analytical and induction methods of texts from both the holy Quran and the prophetic Sunna.